2004
DOI: 10.1108/01443570410558067
|View full text |Cite
|
Sign up to set email alerts
|

Environmental turbulence, strategic orientation

Abstract: Though supply chain integration has emerged in the past several decades as a major foundation for corporate competitiveness, there is a paucity of research devoted to the theory linking the corresponding strategic management notion of vertical integration with the applied concept of supply chain integration. Built on the work of Harrigan, this paper delineates supply chain integration as a multidimensional construct and proposes a model in which environmental turbulence and strategic orientation have a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
3
52
0
4
Order By: Relevance
“…The contingency view suggests that the alignment of the supply chain structure, processes, interrelationships, and governance with the supply chain environment would lead to superior performance (Qrunfleh and Tarafdar, 2014;Stonebraker and Liao 2004;Fisher, 1997;Drazin et. al., 1985).…”
Section: H2 Integration Of Planning Across the Global Supply Networkmentioning
confidence: 98%
“…The contingency view suggests that the alignment of the supply chain structure, processes, interrelationships, and governance with the supply chain environment would lead to superior performance (Qrunfleh and Tarafdar, 2014;Stonebraker and Liao 2004;Fisher, 1997;Drazin et. al., 1985).…”
Section: H2 Integration Of Planning Across the Global Supply Networkmentioning
confidence: 98%
“…Subsequently, decision criteria should aim to consider net revenue maximisation, total emissions minimisation and total risk minimisation, not just for the focal operations within a company but also for the whole supply chain, i.e. to include the supplier's suppliers and customer's customers (Liu andYoung 2004, Stonebraker andLiao 2004). To manage the complexity of global decision-making, it is suggested that both MCDA and LCA methodologies be explored coherently to improve the decision makers' scientific judgements.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Organisational response to environmental turbulence and volatility requires a realignment of competitive priorities (Stonebraker and Liao, 2004). Ward et al (1996) suggest a relationship exists between organisational structure and strategy, manufacturing priorities and the external business environment, with manufacturing priorities occupying a middle position and being subject to influence both internally and externally.…”
Section: Small and Medium Enterprises Strategic Response To Environmementioning
confidence: 99%